Antiviral Activity Effect of Silver Nanoparticles (Agnps) Solution Against the Growth of Infectious Bursal Disease Virus on Embryonated Chicken Eggs with Elisa Test - Pangestika, Rosa; Ernawati, Rahaju (KnE Life Sciences, 2017)
Infectious bursal disease virus is one of the strategic infectious disease in Indonesia. Despite disinfection and vaccination technology has been doing, the cases still frequently occur and it needs another alternative technology to be developed to against IBD virus. This research try to answer the problem, it examines the effect of antiviral activity of silver nanoparticles (AgNPs) solution against the growth of infectious bursal disease virus in embryonated chicken eggs with ELISA Test. The research has two methods, the first method is conducted by mixing a solution of AgNPs and IBD Virus, two hours before inoculated (preventive method) and the second method is the virus inoculated first, 48 hours later the AgNPs solution injected (therapy method). Each method has several dosage of AgNPs solution respectively 0 ppm (positive control 20 ppm, 40 ppm, and 50 ppm). Virus samples taken from the choriallantoic membrane (CAM) and the embryo by crushed method. Results based on the value of OD (optical density) ELISA Test and Statistical Test ANOVA General Linier Models Univariate with Post-Hoc Duncan 5%, both methods have no significant difference (p>0.05), it means the solution of AgNPs has good preventative and therapeutic characteristic. The mean of OD values also showed dosage of 20ppm is most effective dosage in against the growth of the virus, the dosage has significant difference (p<0.05). The decreasing amount of virus in CAM and in embryos were not significantly different (p>0.05), in both CAM and embryo AgNPs solution has good antiviral properties. Keywords : Silver Nanoparticles, Antiviral, Infectious Bursal Disesase, ELISA, Embryonated Chicken Eggs